Memahami Perbedaan Antara Wahyu Dan Ilham : Implikasi Untuk Pendidikan Islam - Ismi Nujaima; Dedi Masri; Muhamad Alfiansyah; Mellani Mellani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research has a goal, specifically to be in position to recognize and comprehend the distinctions among revelation and inspiration and the implications for Islamic education. To see the implications of revelation and inspiration for Islamic education, qualitative research methods can be used. The method of writing this time is study of literature, in which information is gathered via mastering and examining existing theories from several sources in this study. Conclusions of this research indicate that are implications in Islamic education regarding the differences between revelation and inspiration and a connection among the Qur’an and life’s realities.. As for the involvement between revelation and inspiration in Islamic education which is a learning process or learning and teaching process according to islam, that is founded pn the koran and hadith.